An Analytical Study of Urban Mothers’ Knowledge and Using Traditional Health Behaviour for Caring Children with Common Illnesses - Shoukran , Ali; Obaid , Khamess Bander (Kerbala Journal of Nursing and Health Sciences., 2025)
Background: Mothers have a body of knowledge that directly affects children's health, this knowledge is often shaped by factors such as education, standard of living, and economic status. Objective: To evaluate mother Knowledge, and to find relationship between knowledge and sociodemographic data. Method: A cross-sectional study was done covering mothers living in an urban community of kerbala from 2nd December 2024 to 1st April 2025. A total of three primary health center were included in that area. Convenience sampling was used to select the participants. A pre- tested questionnaire was used for data collection from 213 mothers. Data were analysed using descriptive statistics such as mean (SD) and percentages. Chi square test and t test were used for analysis. P value of <0.05 will be considered as statistically significant. Result: The level of knowledge of mothers related to child care with common health problems, it shows that there are significant as the percentage of those with a good level of knowledge reached (65.7%). And shows that there are significant statistical differences between the knowledge of mothers in the urban group and each of their following demographic characteristics: Age (p=0.007), educational level (p=0.005. Conclusion: The study indicates a substantial proportion of mothers have good knowledge regarding child healthcare and present relationship between mother knowledge and demographic data.